2019
DOI: 10.1158/1538-7445.am2019-ddt01-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract DDT01-01: BI 905677: A first-in-class LRP5/6 antagonist targeting Wnt-driven proliferation and immune escape

Abstract: Aberrant Wnt/β-catenin signalling has been shown to play a key role in tumorigenesis and resistance to immunotherapy in several tumor indications. Wnt ligand-mediated signals are transduced by two distinct receptor types, the serpentine receptor Frizzled (FZD) and the closely related single-span transmembrane proteins LRP5 and LRP6. Formation of the FZD-Wnt-LRP5/6 trimeric complex induces phosphorylation of LRP5 or LRP6 intracellular domains leading to inactivation of the β-catenin degradation complex, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Originally designed against FZD7, it was found to bind to 4 additional FZD receptors (FZD1, 2, 5, and 8) and is thought to block Wnt signaling by direct inhibition of Wnt binding. , Recently, Zinzalla et al reported BI905677 ( 20 ) as a first-in-class potent inhibitor of Wnt signaling. BI905677 is a biparatopic antibody comprising two modules that bind unique, nonoverlapping epitopes of LRP5/6 and presumably blocks Wnt signaling by preventing formation of the FZD–Wnt–LRP5/6 trimeric complex . The extracellular secreted protein Dickkopf-1 (DKK1) competes with Wnt proteins for binding to LRP5/6 and functions as a negative regulator of Wnt signaling .…”
Section: Small Molecule Approaches To Modulate Wnt Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally designed against FZD7, it was found to bind to 4 additional FZD receptors (FZD1, 2, 5, and 8) and is thought to block Wnt signaling by direct inhibition of Wnt binding. , Recently, Zinzalla et al reported BI905677 ( 20 ) as a first-in-class potent inhibitor of Wnt signaling. BI905677 is a biparatopic antibody comprising two modules that bind unique, nonoverlapping epitopes of LRP5/6 and presumably blocks Wnt signaling by preventing formation of the FZD–Wnt–LRP5/6 trimeric complex . The extracellular secreted protein Dickkopf-1 (DKK1) competes with Wnt proteins for binding to LRP5/6 and functions as a negative regulator of Wnt signaling .…”
Section: Small Molecule Approaches To Modulate Wnt Signalingmentioning
confidence: 99%
“…BI905677 is a biparatopic antibody comprising two modules that bind unique, nonoverlapping epitopes of LRP5/6 and presumably blocks Wnt signaling by preventing formation of the FZD−Wnt−LRP5/6 trimeric complex. 76 The extracellular secreted protein Dickkopf-1 (DKK1) competes with Wnt proteins for binding to LRP5/6 and functions as a negative regulator of Wnt signaling. 77 Gallocyanine (21, NCI8642) was shown to block the LRP6− DKK1 interaction by SPR through binding to LRP6 (K D 0.47 μM).…”
Section: Wnt Signalingmentioning
confidence: 99%